Gain-scheduled H-infinity observer design for nonlinear stochastic systems with time-delay and actuator saturation - Yin, YanYan; Shi, P.; Liu, F.; Karimi, H. (IEEE, 2012)
In this paper, we propose a method for designing continuous gain-scheduled robust H 8 observer on a class of extended stochastic nonlinear systems subject to time delay and actuator saturation. Initially, gradient linearization procedure is applied to describe such extended nonlinear systems into several model-based linear systems. Next, a robust linear H 8 observer is designed to such linear stochastic models. Subsequently, a convex hull set is investigated and sufficient condition is derived in terms of feedback observer to determine whether a given initial condition belongs to an ellipsoid invariant set. Finally, continuous gain-scheduled approach is employed to design continuous nonlinear observers on the entire extended nonlinear jump system. A simulation example is given to illustrate the effectiveness of developed techniques. © 2012 AACC American Automatic Control Council).